2001
DOI: 10.1159/000046216
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Stroke among Chronic Hemodialysis Patients with Nonrheumatic Atrial Fibrillation

Abstract: In general, nonrheumatic atrial fibrillation is associated with a high risk of stroke. However, its impact on stroke in the setting of chronic hemodialysis treatment is insufficiently addressed in the literature. We assessed the incidence of stroke among 430 chronic hemodialysis patients and the impact of atrial fibrillation and various other potential risk factors on stroke in a retrospective study covering 1,111.16 patient-years. The overall incidence of stroke was 3.78/100 patient-years. Among patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
86
3
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(98 citation statements)
references
References 16 publications
5
86
3
4
Order By: Relevance
“…Stroke rates in warfarin users were statistically no different from rates in nonwarfarin users in a study of patients who had atrial fibrillation and were on dialysis 36 (n ϭ 61). Another study found no difference (P ϭ 0.4) in the incidence of stroke when comparing an "undertreated" population (24% prevalence of warfarin use in patients with atrial fibrillation; n ϭ 127) with patients without atrial fibrillation (n ϭ 349) in the same cohort.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Stroke rates in warfarin users were statistically no different from rates in nonwarfarin users in a study of patients who had atrial fibrillation and were on dialysis 36 (n ϭ 61). Another study found no difference (P ϭ 0.4) in the incidence of stroke when comparing an "undertreated" population (24% prevalence of warfarin use in patients with atrial fibrillation; n ϭ 127) with patients without atrial fibrillation (n ϭ 349) in the same cohort.…”
Section: Discussionmentioning
confidence: 69%
“…34,35 Taken together, warfarin use in dialysis patients may confer additional risk that is not appreciated in patients without renal failure. 2,36 Given the paucity of clinical studies of patients with ESRD, it is currently unresolved whether accepted therapeutic interventions for atrial fibrillation 4 can also be applied to patients who are on dialysis. 2,37 Consequently, we conducted a retrospective cohort study to assess the overall risk-benefit ratio of anticoagulation and antiplatelet therapy in this specific population.…”
mentioning
confidence: 99%
“…For example, in patients with AF, the consequence of a cerebrovascular accident may be considerable. The data pertaining to AF in the HD population is limited to two observational cohort studies, and these provide conflicting estimates of stroke risk (18,19). Half of warfarin-associated major bleeding episodes in this study were sustained by patients who were taking the medication for access preservation.…”
Section: Discussionmentioning
confidence: 91%
“…However, the potential role of other traditional risk factors is somewhat unclear. Hypertension, for example, has been associated with stroke in some 15 but not all 18 studies, and even the findings on the role of AF are discordant, 17,[19][20][21] although the most comprehensive study to date reported that, in the setting of AF, dialysis patients had a 1.8-fold increased risk of stroke compared with non-dialysis-dependent individuals. 22 Such discrepancies in the literature suggested that even basic relationships between common comorbid conditions and stroke risk are not fully understood in the dialysis population.…”
Section: Discussionmentioning
confidence: 99%